Growth Recurring in Preindustrial Spain: Half a Millennium Perspective - Leandro Prados de la Escosura; Carlos Álvarez-Nogal; Carlos Santiago-Caballero (European Historical Economics Society (EHES), 2020)
Research in economic history has lately challenged the Malthusian depiction of preindustrial European economies, highlighting 'efflorescences', 'Smithian' and 'growth recurring' episodes. Do these defining concepts apply to preindustrial Spain? On the basis of new yearly estimates of output and population for nearly 600 years we show that preindustrial Spain was far from stagnant and phases of per capita growth and shrinkage alternated. Population and output per head evolved along supporting the hypothesis of a frontier economy. After a long phase of sustained and egalitarian growth, a collapse in the 1570s opened a new era of sluggish growth and high inequality. The unintended consequences of imperial ambitions in Europe on economic activity, rather than Malthusian forces, help to explain it.
Keywords: E10; N13; O10; O47; 330; Preindustrial Spain; Frontier economy; Black Death; Malthusian; Growth recurring